FACTORS ASSOCIATED WITH CONGENITAL SYPHILIS IN NEWBORNS OF THE INMP 2018-2021 - Fabián Pizarro, Carolyn (2023)
Objective. Determine the factors associated with congenital syphilis in newborns from the INMP between 2018-2021. Materials and methods. Quantitative, observational, analytical, case-control, cross-sectional and retrospective study, the group of cases were 214 neonates with congenital syphilis and 214 controls; A data collection sheet was used and to determine the degree of association, the Chi-square test and the calculation of the Odds ratio (OR) with a confidence interval (CI) at 95% and later a bivariate and multivariate logistic regression analysis were applied. Results. 64.02% of the mothers were between 20 and 35 years old, 82.71% educational level up to secondary school, 99.1% had no complete treatment, 59.3% less than 6 prenatal check-ups, 51.4% were born vaginally; 6.07% hypertensive disorder of pregnancy, 3.74% urinary tract infection, 3.74% chorioamnionitis, 2.34% positive HIV test, 2.80% premature rupture of membranes greater than 24 hours. The neonatal characteristics were 54.2% female, 19.2% prematurity, 11.2% met the laboratory criteria for maternal-neonatal titles, and 1.4% died. 10.3% presented a maculopapular outbreak, 8.9% jaundice, 18.7% low birth weight, 6.5% bone involvement, 44.9% general involvement, 3.3% pneumonia, and 3.3% sepsis. The low weight (OR: 6.434), maternal education up to a higher level (OR: 0.119), complete maternal treatment (OR: 0.002) and premature rupture of membranes greater than 24 hours (OR: 0.140) had a significant association. Conclusion. The factors associated with congenital syphilis in the newborn found were lower maternal educational level, younger age and incomplete maternal treatment.